Lung function after coronary artery surgery using the internal mammary artery and the saphenous vein. Issue 3 (March 1989) - Jenkins, S C; Soutar, S A; Forsyth, A; Keates, J R; Moxham, J
Abstract : Lung volumes and arterial blood gas tensions in patients undergoing coronary artery surgery were compared in 77 patients given an internal mammary artery graft (group 1) and 33 patients given a saphenous vein graft only (group 2). Patients in both groups developed a severe restrictive ventilatory defect after surgery, more pronounced in those receiving an internal mammary artery graft. Mean (SEM) vital capacity in groups 1 and 2 was reduced to 36% (1.2%) and 45% (2.0%) of preoperative values on the second postoperative day (1.56 and 1.85 1 respectively), with some recovery by day 4 to 56% (1.2%) and 63% (2.1%) of preoperative values. The mean (SEM) arterial oxygen tension was 7.34 (0.13) kPa for group 1 and 7.46 (0.20) kPa for group 2 on day 2, rising to 8.39 (0.13) and 9.01 (0.23) kPa on day 4. Analgesic requirements were greater in the group receiving an internal mammary artery graft. Possible explanations for the differences between the effects of the two grafts include the higher frequency of pleurotomy, the placing of pleural drains, and additional surgical trauma when internal mammary artery grafts are used.